Kajian Sumber Bahan Bakar Nabati Berbasis Sorgum Manis - Marcia B. Pabendon; M. Aqil; S. Mas'ud (Puslitbang Tanaman Pangan, 2012)
Sweet sorghum has potential as a crop for producing energy to substitute fossil fuel through the production of ethanol, extracted from the biomass. To produce ethanol not only the stalks of sweet sorghum that can be used, the baggase and the grains are also readily to be processed into ethanol. Sweet sorghum could be grown on the existing dry lands so there is no need for clearing the rainforests. Sweet sorghum is considered easier and cheaper to grow than are other biofuel crops, and it does not require irrigation, so it could be planted in dry areas.